2017
DOI: 10.1007/s11051-017-3816-8
|View full text |Cite
|
Sign up to set email alerts
|

Human health no-effect levels of TiO2 nanoparticles as a function of their primary size

Abstract:  Users may download and print one copy of any publication from the public portal for the purpose of private study or research.  You may not further distribute the material or use it for any profit-making activity or commercial gain  You may freely distribute the URL identifying the publication in the public portal If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(25 citation statements)
references
References 51 publications
2
21
0
Order By: Relevance
“…This discrepancy can mainly be explained by the assumption made by Pini et al 35 to use a no-observed adverse effect level (NOAEL) value for ingestion exposure when determining an EF for inhalation. As reported in Laurent et al 66 , NOAELs differ by several orders of magnitude between the two exposure routes, with regression analyses on available toxicological data for TiO 2 showing a factor of ca. 40 between the two.…”
Section: Effect Factors For Human Toxicitysupporting
confidence: 57%
See 3 more Smart Citations
“…This discrepancy can mainly be explained by the assumption made by Pini et al 35 to use a no-observed adverse effect level (NOAEL) value for ingestion exposure when determining an EF for inhalation. As reported in Laurent et al 66 , NOAELs differ by several orders of magnitude between the two exposure routes, with regression analyses on available toxicological data for TiO 2 showing a factor of ca. 40 between the two.…”
Section: Effect Factors For Human Toxicitysupporting
confidence: 57%
“…To determine ED50 for non-carcinogenic effects of TiO 2 nanoparticles, the study conducted by Laurent et al 66 was used. In this study, a critical review of in vivo studies was performed and relationships between non-observed adverse effect levels (NOAEL) and the primary particle sizes of the particles were investigated.…”
Section: Effect Factors For Human Toxicitymentioning
confidence: 99%
See 2 more Smart Citations
“…Research also investigated the inhalation impacts of P25 TiO 2 NPs to wistar rats and 2 different strains of mice at an average concentration of 10 mg/m 3 , where toxic effects were found on alveolar macrophages and alveolar lung particle clearance (Heinrich et al ). In another study, Laurent et al summarized no‐observed‐adverse‐effect level (NOAEL) and lowest‐observed‐adverse‐effect level (LOAEL) values of TiO 2 NPs in various in vivo studies and predicted the LOAEL (NOAEL) concentrations to be 0.0836 to 4.05 (0.0171–10.5) mg/kg bw per day for exposure through the inhalation route (Laurent et al ). Tsang et al () used 2 studies (Heinrich et al ; Bermudez et al ) combining nano‐TiO 2 and fine‐TiO 2 to calculate carcinogenic ED50, and obtained a value of 1.58 μg/g wet lung (1.43 m 2 /g dry lung).…”
Section: Resultsmentioning
confidence: 99%